SynCro - parsing simple Croatian sentences - Kocijan, Kristina; Bekavac, Božo; Dovedan Han, Zdravko (2010)
In this paper, authors will present derivation of syntactic trees for simple active declarative Croatian sentences. The paper is a continuation of authors PhD thesis in which partial parser and NERC for Croatian language have been implemented and described. This is, to our knowledge, first attempt to build parser for Croatian using NooJ or Intex graphs. At this stage, only parse trees that show the following combinations, are described: subject - verb ; subject - verb - direct object ; subject - verb - direct (and, or) indirect object. In addition to all these combinations, we can detect adverbial phrases of place and of time for any given set and genitive <NP> compliments for all <NP>s in a sentence. Mostly free word order allowed in Croatian sentences presents quite a challenge for building comprehensive syntactic parse trees for them. But grammatical relations in Croatian sentences are usually encoded by a particular case. This fenomena enables easier detection of constituents, even if they are freely reordered (scrambled). The goal of prototype syntactic parser called SynCro is to reach high accuracy in terms of precision while recall is, as less important at this stage, left for further rule expansion. At the end of the paper, the results will be evaluated through precision to show the adequacy of the model.
Projekt MZOS
Projekt MZOS
ENG